Designing assessment indicators (KPIs) for self-assessment of business actor commitment based on Spencer’s competencies - Puspasari, Dewi; Cahyandito, Martha Fani; Harsanto, Budi (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2026)
This study aims to design indicators to assess entrepreneurial commitment based on the Spencer competency framework, to be used as a self-assessment instrument for MSME actors. The research employs a descriptive approach through several stages, including competency identification, development of Key Performance Indicators (KPIs), determination of assessment methods, and weighting of indicators using the Analytic Hierarchy Process (AHP). The competencies applied in this study include organizational commitment, achievement orientation, initiative, self-confidence, and concern for order and quality. The results show that the proposed indicators provide a systematic framework for evaluating entrepreneurial commitment using a Weighted Scoring model. This instrument enables MSME actors to evaluate their level of commitment in managing and developing their businesses. Furthermore, the assessment results can serve as a reference for business development programs and policy formulation aimed at strengthening the sustainability and competitiveness of MSMEs.